A kind of ultra-durable tile adhesive and preparation method thereof
Ultra-durable ceramic tile glue was prepared by polymerizing dopamine on carbon nanotubes and reacting with aluminum nitrate and combining with modified hollow glass microbeads, which solved the problems of weak adhesion and poor durability of existing ceramic tile glue, and achieved Higher bonding performance and building safety.
Patent Information
- Application Number
- CN202410983315.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-22
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-07-22
AI Technical Summary
The existing ceramic tile glue has weak adhesion, poor durability, easy to peel off, and there are problems of pollution and material waste during construction.
Polydopamine-coated carbon nanotubes were prepared by dopamine polymerization and deposited on carbon nanotubes, and reacted with aluminum nitrate and calcined at high temperature to obtain nano-alumina/carbon nanotube composite materials, combined with modified hollow glass microbeads and other materials, Prepare ultra-durable tile glue.
It significantly improves the bonding performance and durability of ceramic tile adhesives, reduces pollution and material waste during construction, and improves building safety.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to a super durable tile adhesive and a preparation method thereof. Background Art
[0002] Ceramic tile adhesive, also known as tile glue, is a modern new type of decoration material specially used for bonding ceramic tiles. Ceramic tiles are widely used in wall decoration materials. In the original ceramic tile laying process, a relatively simple cement mortar is usually used as a binder between the substrate and the ceramic tile. The disadvantages of cement mortar are weak bonding, poor durability, and easy peeling. When mixed on site, the thick layer construction method not only has an unstable ratio, but also causes great pollution to the environment. The construction speed is slow and it also causes waste of materials. The accidental shedding of ceramic tiles also poses a great safety hazard, especially for ceramic tiles used for building exterior walls. Based on the above problems, the present invention proposes a super durable ceramic tile adhesive with excellent bonding properties, which improves the bonding strength of the ceramic tile adhesive to ceramic tiles and buildings, achieving the purpose of durability, saving resources, and improving building safety. Summary of the invention
[0003] The object of the present invention is to provide a super durable tile adhesive and a preparation method thereof, so as to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0005] A super durable tile adhesive. The super durable tile adhesive is prepared by polymerizing and depositing dopamine on carbon nanotubes to obtain polydopamine-coated carbon nanotubes; reacting the polydopamine-coated carbon nanotubes with aluminum nitrate and then calcining at high temperature to obtain nano alumina / carbon nanotube composite materials; treating hollow glass microspheres with γ-methacryloxypropyltrimethoxysilane to obtain pre-modified hollow glass microspheres; polymerizing and growing γ-methacryloxypropyltrimethoxysilane on pre-modified hollow glass microspheres to obtain modified hollow glass microspheres; and mixing Conch Po425R, quartz sand, river sand, fly ash, kaolin, glue powder 4115, cellulose, starch ether, calcium formate, nano alumina / carbon nanotube composite materials, modified hollow glass microspheres and pure water.
[0006] A method for preparing a super durable tile adhesive comprises the following preparation steps:
[0007] (1) polydopamine coated carbon nanotubes and deionized water are mixed uniformly at a mass ratio of 1:(8-10), aluminum nitrate is added in an amount 2-3 times the mass of the polydopamine coated carbon nanotubes, and the mixture is stirred at 10-30° C. and 300-500 r / min for 30-40 min, and an ammonia aqueous solution with a mass fraction of 10-12% and a mass fraction of 3-4 times the mass of the polydopamine coated carbon nanotubes is added dropwise at a uniform rate within 30 min, and the mixture is stirred and reacted for 35-45 min, filtered, washed with deionized water for 3-5 times, dried at 55-65° C. for 7-9 h, and calcined in a muffle furnace at 350-360° C. for 2-3 h to obtain a nano-alumina / carbon nanotube composite material;
[0008] (2) The hollow glass microspheres and the silane hydrolyzate are uniformly mixed in a mass ratio of 1:10-12, stirred at 70-80°C and 300-500 r / min for 2-3 h, cooled to room temperature, centrifuged, washed with anhydrous ethanol and deionized water for 3-5 times each, and dried at 50-60°C for 5-7 h under vacuum conditions to obtain pre-modified hollow glass microspheres; the pre-modified hollow glass microspheres, γ-methacryloxypropyltrimethoxysilane, and toluene are uniformly mixed in a mass ratio of 1:(0 .6~0.8):(8~10) mix evenly to prepare a mixed solution; pass nitrogen, at 70~80℃, 200~300r / min stirring conditions, add 0.04~0.06 times the mass of the initiator solution to the mixed solution at a uniform rate within 20min, continue stirring for 5~6h, cool to room temperature, filter and wash with methanol and deionized water for 3~5 times respectively, and dry at 40~50℃ under vacuum conditions for 5~7h to obtain modified hollow glass microspheres;
[0009] (3) Conch Po425R, quartz sand, river sand, fly ash, kaolin, glue powder 4115, cellulose, starch ether, early strength agent, nano-alumina / carbon nanotube composite material, and modified hollow glass microspheres are mixed evenly in a mass ratio of 350:350:230:(45-55):12.5:13:(2.5-3.5):(0.7-0.9):(4-6):(2-3):(30-40) to prepare a tile adhesive mixture, and stir at 10-30°C and 600-700 r / min for 8-10 min, then add pure water in an amount of 0.4-0.6 times the mass of the tile adhesive mixture, mix evenly, and prepare an ultra-durable tile adhesive.
[0010] As an optimization, the polydopamine-coated carbon nanotubes in step (1) are prepared by uniformly mixing carbon nanotubes and deionized water in a mass ratio of 1:(40-50), ultrasonically dispersing for 35-45 minutes, adding dopamine in an amount of 2-3 times the mass of the carbon nanotubes, continuing ultrasonically dispersing for 10-20 minutes, adjusting the pH to 8-9 with Tris-HCl buffer, stirring at 10-30° C. and 300-500 r / min for 20-24 hours, filtering, washing with deionized water for 3-5 times, and drying at 55-65° C. for 7-9 hours.
[0011] As an optimization, the silane hydrolyzate in step (2) is prepared by uniformly mixing γ-methacryloxypropyltrimethoxysilane and anhydrous ethanol in a mass ratio of 1:40-50, adding glacial acetic acid to adjust the pH to 5-6, and stirring at 50-60° C. and 300-500 r / min for 1-2 hours to obtain a silane hydrolyzate.
[0012] As an optimization, the initiator solution in step (2) is prepared by mixing azobisisobutyronitrile and toluene in a mass ratio of 1:(20-30) to form an initiator solution.
[0013] As an optimization, the mesh size of the hollow glass microspheres in step (2) is 200.
[0014] As an optimization, the molecular weight of the cellulose in step (3) is 10,000.
[0015] As an optimization, the early strength agent in step (3) is calcium formate.
[0016] As an optimization, the model of the starch ether in step (3) is FP6.
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0018] When preparing the super durable tile adhesive, the present invention comprises the following steps: polymerizing and depositing dopamine on carbon nanotubes to obtain polydopamine-coated carbon nanotubes; reacting the polydopamine-coated carbon nanotubes with aluminum nitrate and then calcining at high temperature to obtain nano alumina / carbon nanotube composite materials; treating hollow glass microspheres with γ-methacryloxypropyltrimethoxysilane to obtain pre-modified hollow glass microspheres; polymerizing and growing γ-methacryloxypropyltrimethoxysilane on the pre-modified hollow glass microspheres to obtain modified hollow glass microspheres; and mixing conch Po425R, quartz sand, river sand, fly ash, kaolin, glue powder 4115, cellulose, starch ether, calcium formate, nano alumina / carbon nanotube composite materials, modified hollow glass microspheres and pure water to obtain the super durable tile adhesive.
[0019] Firstly, dopamine is polymerized and deposited on carbon nanotubes to prepare polydopamine-coated carbon nanotubes, and a large number of amino groups are introduced into the carbon nanotubes; the amino groups on the polydopamine-coated carbon nanotubes can react with the aluminum ions in aluminum nitrate to fix the aluminum ions on the carbon nanotubes; the aluminum ions then react with ammonia water to produce aluminum hydroxide by acid-base neutralization reaction, and finally the aluminum hydroxide is converted into aluminum oxide by high-temperature sintering, and the aluminum oxide is successfully loaded onto the carbon nanotubes; the aluminum oxide can react with the calcium hydroxide released during the hydration of cement clinker to produce volcanic ash gel, thereby reducing the void ratio between cement particles, increasing the contact area between the tile adhesive itself, the tile adhesive and the building and the tile, and significantly improving the bonding performance of the super-durable tile adhesive; and the carbon nanotubes are loaded with nano-alumina on the surface, so that the carbon nanotubes can be well dispersed in the super-durable tile adhesive, and combined with the above-mentioned reaction of nano-alumina, the bonding force between the carbon nanotubes and the concrete is enhanced, so that its reinforcing performance can be better exerted.
[0020] Secondly, the hollow glass microspheres are treated with γ-methacryloxypropyltrimethoxysilane to obtain pre-modified hollow glass microspheres, and carbon-carbon double bonds are introduced into the vitrified microspheres; γ-methacryloxypropyltrimethoxysilane is polymerized and grown on the pre-modified hollow glass microspheres to obtain modified hollow glass microspheres, and a large amount of organosilicon polyester is introduced into the surface of the hollow glass microspheres; under the action of cement hydration heat, the organosilicon polyester will hydrolyze to form a large amount of silanol, which can form silicon-oxygen connections with stones or themselves to form an organic / inorganic hybrid network structure, making the structure of the tile adhesive tighter and firmer, and further The bonding performance of the super-durable tile adhesive is improved one step further; hollow glass microspheres are a high-performance material, which are tiny spherical particles made of borosilicate glass material with a hollow structure inside. The hollow glass microspheres have high heat reflectivity and reflect visible light and near-infrared light in sunlight multiple times. The reflectivity is very high, which is beneficial to thermal insulation and heat insulation. It can provide excellent thermal insulation and fire resistance in the construction field. Through surface modification, the hollow glass microspheres are evenly dispersed in the tile adhesive and are tightly connected with the components in the tile adhesive, giving the super-durable tile adhesive excellent thermal insulation properties. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] Example 1
[0023] A method for preparing a super durable tile adhesive, the method comprising the following preparation steps:
[0024] (1) Mix carbon nanotubes and deionized water at a mass ratio of 1:40, ultrasonically disperse for 35 minutes, add dopamine twice the mass of the carbon nanotubes, continue ultrasonically disperse for 10 minutes, adjust the pH to 8 with Tris-HCl buffer, stir at 10°C, 300 r / min for 24 hours, filter, wash with deionized water three times, and dry at 55°C for 9 hours to obtain polydopamine-coated carbon nanotubes; Mix polydopamine-coated carbon nanotubes and deionized water at a mass ratio of 1:8, add aluminum nitrate twice the mass of the polydopamine-coated carbon nanotubes, stir at 10°C, 300 r / min for 40 minutes, uniformly add 10% ammonia aqueous solution three times the mass of the polydopamine-coated carbon nanotubes within 30 minutes, continue stirring for 35 minutes, filter, wash with deionized water three times, dry at 55°C for 9 hours, and calcine at 350°C in a muffle furnace for 3 hours to obtain a nano-alumina / carbon nanotube composite material;
[0025] (2) γ-methacryloxypropyltrimethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:40, glacial acetic acid was added to adjust the pH to 5, and the mixture was stirred at 50°C and 300 r / min for 2 h to obtain a silane hydrolyzate; hollow glass microspheres and silane hydrolyzate were mixed at a mass ratio of 1:10, and the mixture was stirred at 70°C and 300 r / min for 3 h, cooled to room temperature, centrifuged, washed with anhydrous ethanol and deionized water for 3 times each, and dried at 50°C for 7 h under vacuum conditions to obtain pre-modified hollow glass microspheres; the pre-modified hollow glass microspheres and γ-methacryloxypropyltrimethoxysilane were mixed at a mass ratio of 1:10, and the mixture was stirred at 70°C and 300 r / min for 3 h, cooled to room temperature, centrifuged, washed with anhydrous ethanol and deionized water for 3 times each, and dried at 50°C for 7 h under vacuum conditions to obtain pre-modified hollow glass microspheres; the pre-modified hollow glass microspheres and γ- Methacryloxypropyltrimethoxysilane and toluene are mixed evenly in a mass ratio of 1:0.6:8 to prepare a mixed solution, and azobisisobutyronitrile and toluene are mixed evenly in a mass ratio of 1:20 to prepare an initiator solution; nitrogen is passed through, and under stirring conditions of 70°C and 200r / min, an initiator solution 0.04 times the mass of the mixed solution is uniformly added dropwise to the mixed solution within 20min, stirring is continued for 6h, cooled to room temperature, filtered, and washed with methanol and deionized water for 3 times respectively, and dried at 40°C for 7h under vacuum conditions to obtain modified hollow glass microspheres;
[0026] (3) Conch Po425R, quartz sand, river sand, fly ash, kaolin, glue powder 4115, cellulose, starch ether, calcium formate, nano-alumina / carbon nanotube composite material, and modified hollow glass microspheres were mixed at a mass ratio of 350:350:230:45:12.5:13:2.5:0.7:4:2:30 to prepare a tile adhesive mixture, stirred at 10°C and 600 r / min for 10 min, and then 0.4 times the mass of pure water of the tile adhesive mixture was added and mixed to prepare an ultra-durable tile adhesive.
[0027] Example 2
[0028] A method for preparing a super durable tile adhesive, the method comprising the following preparation steps:
[0029] (1) The carbon nanotubes and deionized water were mixed at a mass ratio of 1:45, ultrasonically dispersed for 40 minutes, dopamine was added in an amount 2.5 times the mass of the carbon nanotubes, ultrasonically dispersed for 15 minutes, the pH was adjusted to 8.5 with Tris-HCl buffer, stirred at 20°C and 400 r / min for 22 hours, filtered, washed with deionized water for 4 times, and dried at 60°C for 8 hours to obtain polydopamine-coated carbon nanotubes; the polydopamine-coated carbon nanotubes and deionized water were mixed at a mass ratio of 1:45, ultrasonically dispersed for 40 minutes, dopamine was added in an amount 2.5 times the mass of the carbon nanotubes, ultrasonically dispersed for 15 minutes, the pH was adjusted to 8.5 with Tris-HCl buffer, the mixture was stirred at 20°C and 400 r / min for 22 hours, filtered, washed with deionized water for 4 times, and dried at 60°C for 8 hours to obtain polydopamine-coated carbon nanotubes. 9. Mix well, add aluminum nitrate with a mass fraction of 2.5 times that of the polydopamine-coated carbon nanotubes, stir and react at 20°C, 400r / min for 35min, uniformly add 11% ammonia aqueous solution with a mass fraction of 3.5 times that of the polydopamine-coated carbon nanotubes within 30min, continue stirring and reacting for 40min, filter, wash with deionized water 4 times, dry at 60°C for 8h, place in a muffle furnace and calcine at 355°C for 2.5h to obtain a nano-alumina / carbon nanotube composite material;
[0030] (2) γ-methacryloxypropyltrimethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:45, glacial acetic acid was added to adjust the pH to 5.5, and the mixture was stirred at 55°C and 400 r / min for 1.5 h to obtain a silane hydrolyzate; hollow glass microspheres and silane hydrolyzate were mixed at a mass ratio of 1:11, and the mixture was stirred at 75°C and 400 r / min for 2.5 h, cooled to room temperature, centrifuged, washed with anhydrous ethanol and deionized water for 4 times each, and dried at 55°C for 6 h under vacuum conditions to obtain pre-modified hollow glass microspheres; the pre-modified hollow glass microspheres, γ-methacryloxypropyltrimethoxysilane and toluene are mixed evenly in a mass ratio of 1:0.7:9 to prepare a mixed solution; azobisisobutyronitrile and toluene are mixed evenly in a mass ratio of 1:25 to prepare an initiator solution; nitrogen is passed through, and under stirring conditions of 75°C and 250r / min, 0.05 times the mass of the initiator solution is uniformly added dropwise to the mixed solution within 20min, stirring is continued for 5.5h, cooled to room temperature, filtered, and washed with methanol and deionized water for 4 times respectively, and dried at 45°C for 6h under vacuum conditions to obtain modified hollow glass microspheres;
[0031] (3) Conch Po425R, quartz sand, river sand, fly ash, kaolin, glue powder 4115, cellulose, starch ether, calcium formate, nano-alumina / carbon nanotube composite material, and modified hollow glass microspheres were mixed at a mass ratio of 350:350:230:50:12.5:13:3:0.8:5:2.5:35 to prepare a tile adhesive mixture, stirred at 20°C and 650 r / min for 9 min, and then 0.5 times the mass of pure water of the tile adhesive mixture was added and mixed to prepare an ultra-durable tile adhesive.
[0032] Example 3
[0033] A method for preparing a super durable tile adhesive, the method comprising the following preparation steps:
[0034] (1) Mix carbon nanotubes and deionized water at a mass ratio of 1:50, ultrasonically disperse for 45 minutes, add dopamine 3 times the mass of the carbon nanotubes, continue ultrasonically disperse for 20 minutes, adjust the pH to 9 with Tris-HCl buffer, stir at 30°C, 500 r / min for 20 hours, filter, wash with deionized water 5 times, and dry at 65°C for 7 hours to obtain polydopamine-coated carbon nanotubes; Mix polydopamine-coated carbon nanotubes and deionized water at a mass ratio of 1:10, add aluminum nitrate 3 times the mass of the polydopamine-coated carbon nanotubes, stir at 30°C, 500 r / min for 30 minutes, uniformly add 12% ammonia aqueous solution 4 times the mass of the polydopamine-coated carbon nanotubes within 30 minutes, continue stirring for 35 minutes, filter, wash with deionized water 5 times, dry at 65°C for 7 hours, and calcine at 360°C in a muffle furnace for 2 hours to obtain a nano-alumina / carbon nanotube composite material;
[0035] (2) γ-methacryloxypropyltrimethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:50, glacial acetic acid was added to adjust the pH to 6, and the mixture was stirred at 60°C and 500 r / min for 1 hour to obtain a silane hydrolyzate; hollow glass microspheres and silane hydrolyzate were mixed at a mass ratio of 1:12, and the mixture was stirred at 80°C and 500 r / min for 2 hours, cooled to room temperature, centrifuged, washed with anhydrous ethanol and deionized water for 5 times each, and dried at 60°C for 5 hours under vacuum conditions to obtain pre-modified hollow glass microspheres; the pre-modified hollow glass microspheres and γ-methacryloxypropyltrimethoxysilane were mixed at a mass ratio of 1:12, and the mixture was stirred at 80°C and 500 r / min for 2 hours to obtain a pre-modified hollow glass microspheres. Acryloxypropyltrimethoxysilane and toluene are mixed evenly in a mass ratio of 1:0.8:10 to prepare a mixed solution; azobisisobutyronitrile and toluene are mixed evenly in a mass ratio of 1:20 to prepare an initiator solution; nitrogen is passed through, and under stirring conditions of 80°C and 300r / min, an initiator solution of 0.06 times the mass of the mixed solution is uniformly added dropwise to the mixed solution within 20min, stirring is continued for 5h, cooled to room temperature, filtered, and washed with methanol and deionized water for 5 times respectively, and dried at 50°C for 5h under vacuum conditions to obtain modified hollow glass microspheres;
[0036] (3) Conch Po425R, quartz sand, river sand, fly ash, kaolin, glue powder 4115, cellulose, starch ether, calcium formate, nano-alumina / carbon nanotube composite material, and modified hollow glass microspheres were mixed evenly in a mass ratio of 350:350:230:55:12.5:13:3.5:0.9:6:3:40 to prepare a tile adhesive mixture, stirred at 30°C and 700 r / min for 8 min, and then 0.6 times the mass of pure water of the tile adhesive mixture was added and mixed evenly to prepare an ultra-durable tile adhesive.
[0037] Comparative Example 1
[0038] The difference between the preparation method of the ultra-durable tile adhesive of Comparative Example 1 and Example 2 is that step (1) is not performed, and step (3) is modified as follows: Conch Po425R, quartz sand, river sand, fly ash, kaolin, glue powder 4115, cellulose, starch ether, calcium formate, carbon nanotubes, and modified hollow glass microspheres are mixed uniformly in a mass ratio of 350:350:230:50:12.5:13:3:0.8:5:2.5:35 to prepare a tile adhesive mixture, stir at 20°C and 650r / min for 9 minutes, then add 0.5 times the mass of pure water of the tile adhesive mixture, mix uniformly, and prepare an ultra-durable tile adhesive. The remaining steps are the same as those of Example 2.
[0039] Comparative Example 2
[0040] The difference between the preparation method of the ultra-durable tile adhesive of Comparative Example 2 and Example 2 is that step (2) is not performed, and step (3) is modified as follows: Conch Po425R, quartz sand, river sand, fly ash, kaolin, glue powder 4115, cellulose, starch ether, calcium formate, nano-alumina / carbon nanotube composite material, and hollow glass microspheres are mixed uniformly in a mass ratio of 350:350:230:50:12.5:13:3:0.8:5:2.5:35 to prepare a tile adhesive mixture, stir at 20°C and 650r / min for 9 minutes, then add 0.5 times the mass of pure water of the tile adhesive mixture, mix uniformly, and prepare an ultra-durable tile adhesive. The remaining steps are the same as those of Example 2.
[0041] Comparative Example 3
[0042] The preparation method of the ultra-durable tile adhesive of Comparative Example 3 is different from that of Example 2 in that step (2) is not performed, and step (3) is modified as follows: Conch Po425R, quartz sand, river sand, fly ash, kaolin, glue powder 4115, cellulose, starch ether, calcium formate, and nano-alumina / carbon nanotube composite material are mixed uniformly in a mass ratio of 350:350:230:50:12.5:13:3:0.8:5:2.5 to prepare a tile adhesive mixture, stir at 20°C and 650r / min for 9 minutes, then add 0.5 times the mass of pure water of the tile adhesive mixture, mix uniformly, and prepare an ultra-durable tile adhesive. The remaining steps are the same as those of Example 2.
[0043] Test Example 1
[0044] Adhesion performance test
[0045] Test method: The bonding strength of the examples and comparative examples was tested according to JCT / 547-2017 "Ceramic Tile Adhesives". The results are shown in Table 1.
[0046] Table 1
[0047] Bond strength (MPa) Bond strength (MPa) Example 1 1.67 Comparative Example 1 1.23 Example 2 1.72 Comparative Example 2 1.14 Example 3 1.64 Comparative Example 3 1.09
[0048] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the super durable tile adhesive prepared by the present invention has good bonding performance.
[0049] By comparison, the bonding strength of Examples 1 to 3 is greater than that of Comparative Example 1, indicating that dopamine is polymerized and deposited on carbon nanotubes to prepare polydopamine-coated carbon nanotubes, and a large number of amino groups are introduced on the carbon nanotubes; the amino groups on the polydopamine-coated carbon nanotubes can undergo a coordination reaction with the aluminum ions in aluminum nitrate to fix the aluminum ions on the carbon nanotubes; the aluminum ions then undergo an acid-base neutralization reaction with ammonia water to generate aluminum hydroxide, and finally high-temperature sintering converts the aluminum hydroxide into aluminum oxide, and the aluminum oxide is successfully loaded onto the carbon nanotubes; the aluminum oxide can undergo a volcanic ash reaction with the calcium hydroxide released during the hydration of cement clinker to generate a hydrated calcium aluminate gel, thereby reducing the void ratio between cement particles, increasing the contact area between the tile adhesive itself and the tile adhesive and the building and tiles, and significantly improving the bonding performance of the super-durable tile adhesive.
[0050] By comparison, the bonding strength of Examples 1 to 3 is greater than that of Comparative Examples 2 to 3, indicating that the hollow glass microspheres are treated with γ-methacryloxypropyltrimethoxysilane to obtain pre-modified hollow glass microspheres, and carbon-carbon double bonds are introduced into the vitrified microspheres; γ-methacryloxypropyltrimethoxysilane is polymerized and grown on the pre-modified hollow glass microspheres to obtain modified hollow glass microspheres, and a large amount of organosilicon polyester is introduced onto the surface of the hollow glass microspheres; under the action of cement hydration heat, the organosilicon polyester will hydrolyze to form a large amount of silanol, and the silanol can form silicon-oxygen connections with stones or itself to form an organic / inorganic hybrid network structure, so that the structure of the tile adhesive is tighter and firmer, further improving the bonding performance of the super-durable tile adhesive.
[0051] Test Example 2
[0052] Thermal insulation performance test
[0053] Test method: The thermal conductivity of the examples and comparative examples was tested with reference to GB / T10294-2008 "Determination of stable thermal resistance and related properties of thermal insulation materials - heat flow meter method". The results are shown in Table 2.
[0054] Table 2
[0055] Thermal conductivity W / (m·k) Thermal conductivity W / (m·k) Example 1 0.086 Comparative Example 1 0.093 Example 2 0.079 Comparative Example 2 0.124 Example 3 0.081 Comparative Example 3 0.148
[0056] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the super durable tile adhesive prepared by the present invention has good thermal insulation performance.
[0057] By comparison, the thermal conductivity of Examples 1 to 3 is less than that of Comparative Examples 2 to 3, indicating that the hollow glass microspheres are treated with γ-methacryloxypropyltrimethoxysilane to prepare pre-modified hollow glass microspheres, and carbon-carbon double bonds are introduced into the vitrified microspheres; γ-methacryloxypropyltrimethoxysilane is polymerized and grown on the pre-modified hollow glass microspheres to prepare modified hollow glass microspheres, and a large amount of organosilicon polyester is introduced into the surface of the hollow glass microspheres; under the action of cement hydration heat, the organosilicon polyester will hydrolyze to form a large amount of silanol, which can form silicon-oxygen connections with stones or themselves to form organic / inorganic The organic hybrid network structure makes the structure of the tile adhesive tighter and firmer; hollow glass microspheres are a high-performance material, which are tiny spherical particles made of borosilicate glass material with a hollow structure inside. The hollow glass microspheres have high heat reflection properties and reflect visible light and near-infrared light in sunlight multiple times. The reflectivity is very high, which is beneficial to thermal insulation and heat insulation. It can provide excellent thermal insulation and fire resistance in the construction field. Through surface modification, the hollow glass microspheres are evenly dispersed in the tile adhesive and are tightly connected with the components in the tile adhesive, giving the super-durable tile adhesive excellent thermal insulation properties.
[0058] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a super durable tile adhesive, characterized in that: The method comprises the following preparation steps: (1) Polydopamine-coated carbon nanotubes and deionized water were mixed at a mass ratio of 1:(8-10), and aluminum nitrate was added in an amount 2-3 times the mass of the polydopamine-coated carbon nanotubes. The mixture was stirred at 10-30°C and 300-500 r / min for 30-40 min. A 10-12% aqueous ammonia solution in an amount 3-4 times the mass of the polydopamine-coated carbon nanotubes was added dropwise at a constant rate within 30 min. The mixture was stirred and reacted for 35-45 min. The mixture was filtered, washed with deionized water for 3-5 times, dried at 55-65°C for 7-9 h, and calcined in a muffle furnace at 350-360°C for 2-3 h to obtain a nano-alumina / carbon nanotube composite material. (2) The hollow glass microspheres and the silane hydrolyzate were mixed uniformly in a mass ratio of 1:10-12, stirred at 70-80°C and 300-500 r / min for 2-3 h, cooled to room temperature, centrifuged, washed with anhydrous ethanol and deionized water for 3-5 times respectively, and dried at 50-60°C for 5-7 h under vacuum conditions to obtain pre-modified hollow glass microspheres; the pre-modified hollow glass microspheres, γ-methacryloxypropyltrimethoxysilane and toluene were mixed uniformly in a mass ratio of 1:(0 .6~0.8):(8~10) mix well to prepare a mixed solution; pass nitrogen, at 70~80℃, 200~300r / min stirring conditions, add 0.04~0.06 times the mass of the initiator solution to the mixed solution at a uniform rate within 20min, continue stirring for 5~6h, cool to room temperature, filter and wash with methanol and deionized water for 3~5 times each, and dry at 40~50℃ under vacuum conditions for 5~7h to obtain modified hollow glass microspheres; (3) Conch Po425R, quartz sand, river sand, fly ash, kaolin, glue powder 4115, cellulose, starch ether, early strength agent, nano-alumina / carbon nanotube composite material, and modified hollow glass microspheres were mixed evenly in a mass ratio of 350:350:230:(45-55):12.5:13:(2.5-3.5):(0.7-0.9):(4-6):(2-3):(30-40) to prepare a tile adhesive mixture, stirred at 10-30°C and 600-700 r / min for 8-10 min, and then 0.4-0.6 times the mass of pure water of the tile adhesive mixture was added and mixed evenly to prepare a super durable tile adhesive; The polydopamine-coated carbon nanotubes in step (1) are prepared by uniformly mixing carbon nanotubes and deionized water in a mass ratio of 1:(40-50), ultrasonically dispersing for 35-45 minutes, adding dopamine in an amount of 2-3 times the mass of the carbon nanotubes, continuing ultrasonically dispersing for 10-20 minutes, adjusting the pH to 8-9 with Tris-HCl buffer, stirring at 10-30° C. and 300-500 r / min for 20-24 hours, filtering, washing with deionized water for 3-5 times, and drying at 55-65° C. for 7-9 hours.
2. The method for preparing a super durable tile adhesive according to claim 1, characterized in that: The silane hydrolyzate in step (2) is prepared by uniformly mixing γ-methacryloxypropyltrimethoxysilane and anhydrous ethanol in a mass ratio of 1:40-50, adding glacial acetic acid to adjust the pH to 5-6, and stirring at 50-60° C. and 300-500 r / min for 1-2 hours to obtain a silane hydrolyzate.
3. The method for preparing a super durable tile adhesive according to claim 1, characterized in that: The initiator solution in step (2) is prepared by mixing azobisisobutyronitrile and toluene in a mass ratio of 1:(20-30) to form an initiator solution.
4. The method for preparing a super durable tile adhesive according to claim 1, characterized in that: The mesh size of the hollow glass microspheres in step (2) is 200.
5. The method for preparing a super durable tile adhesive according to claim 1, characterized in that: The molecular weight of the cellulose in step (3) is 10,000.
6. The method for preparing a super durable tile adhesive according to claim 1, characterized in that: The early strength agent in step (3) is calcium formate.
7. The method for preparing a super durable tile adhesive according to claim 1, characterized in that: The model of the starch ether in step (3) is FP6.
8. A super durable tile adhesive prepared according to the method for preparing super durable tile adhesive according to any one of claims 1 to 7.
Citation Information
Patent Citations
Energy-saving tile adhesive containing ceramic microspheres and preparation method of tile adhesive
CN107500647A
Glass microbead thermal insulation mortar and preparation method thereof
CN108585701A